2000
DOI: 10.1034/j.1600-051x.2000.027004231.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental and periodontal status of Sjögren's syndrome

Abstract: No significant,difference could be detected concerning the dental and periodontal status of SS patients, compared with that of patients with other immune diseases as well as with that of controls who had subjective xerostomia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 10 publications
5
56
1
2
Order By: Relevance
“…No differences distinguished these 2 groups with respect to the periodontal indices, except that the plaque index was lower in patients with primary SS than in subjects with xerostomia. Our observation reinforces results of the study in which patients with primary SS were compared with control subjects who had "a subjective feeling of xerostomia" (3).…”
Section: Results and Conclusionsupporting
confidence: 74%
See 1 more Smart Citation
“…No differences distinguished these 2 groups with respect to the periodontal indices, except that the plaque index was lower in patients with primary SS than in subjects with xerostomia. Our observation reinforces results of the study in which patients with primary SS were compared with control subjects who had "a subjective feeling of xerostomia" (3).…”
Section: Results and Conclusionsupporting
confidence: 74%
“…Lower plaque indices have been described in these patients compared with normal controls (2), but no differences in other periodontal scores between these 2 groups of individuals were observed. In sharp contrast, Boutsi et al (3) reported that the specific periodontal indices were unaffected in their patients with primary SS. Such a discrepancy between the plaque index and other periodontal indices is consistent with our finding that, in contrast to subjects with xerostomia, in patients with primary SS there was no correlation between the plaque index and the other periodontal indices.…”
Section: Results and Conclusionmentioning
confidence: 82%
“…3 Compromised salivary flow and consequent higher dental plaque index are associated with increased prevalence of chronic periodontitis in pSS patients. 4,5,6 In fact, Celenligil et al 7 observed a higher presence of serum antibodies against periodontal pathogens such as Aggregatibacter actinomycetemcomitans (Aa) and Porphyromonas gingivalis (Pg) in pSS patients, compared with healthy subjects with severe chronic periodontitis. Interestingly, Lugonja et al 8 also found raised serum antibody levels to Prevotella denticola in pSS patients, compared with a non-inflammatory group of patients with osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Xerostomic patients complain mostly about burning mouth, loss of taste, difficulty in swallowing, unpleasant taste and odor, oral dryness, increased thirst, chewing, speaking, gastroesophageal reflux, oral breathing, malfunction of removable prosthesis and sensitive teeth (49)(50)(51)(52)(53)(54) with the interaction of the glandular cell with its extracellular matrix sectional descriptive observational study that patients with SS have voice, speech and swallowing abnormalities, not only associated with to xerosis but perhaps also to neurological abnormalities, probably secondary to the syndrome (55). On the other hand, subjective xerostomia has been reported in higher percentages (75.18% to 91.84%) in patients with SS (56). In addition to that, Skopouli et al showed that the rate of dry mouth increased from 41% of patients at initial diagnosis to 84% 10 years after diagnosis (57).…”
Section: Xerostomia and Treatmentmentioning
confidence: 99%
“…Mathews et al mentioned in their excellent review article named 'Oral manifestations of Sjögren's syndrome' that dental plaque, consisting of more than 500 species of bacteria in a mature state, is a complex biofilm of microbes that adheres to the surfaces of teeth and provides a reservoir for oral microbial pathogens (61,63,64 Boutsi et al mentioned in their study investigating dental and periodontal status of patients with SS that the number of cervical decay lesions correlated negatively with the salivary flow (56). It is known that because of reduced salivary flow, bacterial plaque accumulates more rapidly on the tooth surface and especially at the marginal gingiva and crevicular areas which results in a higher prevalence of cervical caries (56).…”
Section: Risk Of Dental Caries and Erosionsmentioning
confidence: 99%